EVALUASI USABILITY WEBSITE MENGGUNAKAN METODE HEURISTIC EVALUATION STUDI KASUS: (WEBSITE DINAS PEKERJAAN UMUM KOTA XYZ) - Amalia Oktafina; Febiyanti Arifatul Jannah; Muchamad Fahrur Rizky; Muhammad Verrel Ferly; Yansen Dharma Tangtobing; Sri Rahayu Natasia (Universitas Islam Balitar, 2021)
The very rapid development of information technology in this era allows most people to access various kinds of information in other parts of the world through a network called the internet. However, to access this information, other things are needed, such as a website address that contains the desired information and an interface to display the information desired by the user. Every user must have a different experience when interacting with an interface, this is called the user experience. By knowing what experiences are experienced by users, developers can find out the various weaknesses and strengths that exist on the website created so that developers can update their website according to user needs. The evaluation carried out in this study uses the heuristic evaluation method, where this evaluation method is carried out to find usability problems that exist on the XYZ City Public Works Office website by referring to 10 heuristic principles to produce effective and efficient improvements. The evaluation stages carried out in this study are establishing requirements, design alternatives, prototyping, and conclusions. The results of this study were found 17 problems and 17 recommendations for improvements made based on the discovery of problems that exist in the object of this study even though there are 2 principles that have no problems in it. Most problems were found on the principles of flexibility and efficiency of use. The problems that have severity rating 4 are 3 problems, severity rating 3 is 4 problems, severity rating 2 is 7 problems and severity rating 0 is 1 problem.